Antenatally detected abdominal cyst: Does cyst size and nature determine postnatal symptoms and outcome?. (August 2020) - Lewis, Sarah; Walker, Jane; McHoney, Merrill
Abstract: Background: The outcome of antenatally detected fetal intra-abdominal cysts is highly variable and challenging to predict. Antenatal ultrasound scans may be of value in predicting postnatal outcome. Aims: To report antenatal and postnatal course of fetal intra-abdominal cysts identified on antenatal ultrasound and establish the value of cyst dimensions for predicting outcome. Study design: Retrospective observational study. Subjects: All intra-abdominal cysts diagnosed in a single centre between 2013 and 2019. Outcome measures: Cyst characteristics were recorded from radiological reports and postnatal diagnosis and outcomes documented. Growth characteristics were identified to distinguish different diagnosis. The maximum antenatal diameter of all cysts was identified and the best cut-off diameter to predict whether a cyst would persist postnatally or require surgery was identified. Best cut-off values were identified using Youden index. Results: Of the 38 cysts identified on antenatal ultrasound, 24 (63%) persisted postnatally, 8 required surgery (21%) and 4 (11%) were not considered an intra-abdominal cyst postnatally. Ovarian cyst and duplication cyst may have different growth characteristics. In the prediction of cysts persisting postnatally, the area under the ROC curve (AUC) was 0.81 (95% CI, 0.66–0.95). Two cut off values were identified, 37.5 mm (50% sensitivity, specificity 100%, Youden's index 0.50) and 28.5 mm (sensitivity 65%, specificity 85%, Youden's index 0.50). In the prediction of surgery, no optimal diameter was found; AUC was 0.57 (95% CI, 0.34–0.81). Conclusions: Maximum antenatal cyst diameter is useful for the prediction of whether a cyst will persist postnatally but not for the prediction of surgery. Highlights: Diagnostic accuracy from the antenatal USS can be as high as 67 to 80%. Cyst from different aetiologies may demonstrate different intrauterine growth characteristics. Maximum cyst diameter greater than 37 mm in-utero is predictive of persistence postnatally. Cyst size was not predictive of postoperative symptoms or the need for surgery.